Practical Language Processing for Virtual Humans - Leuski, Anton; Traum, David (Proceedings of the AAAI Conference on Artificial Intelligence, 2010)
NPCEditor is a system for building a natural language processing component for virtual humans capable of engaging a user in spoken dialog on a limited domain. It uses a statistical language classification technology for mapping from user’s text input to system responses. NPCEditor provides a user-friendly editor for creating effective virtual humans quickly. It has been deployed as a part of various virtual human systems in several applications.